Integration of network pharmacology, transcriptomics, and experimental verification to investigate the mechanism of action of cepharanthine hydrochloride against prostate cancer - Zongming Dong; Xiaosa Chang; Xing Luo; Hui Li; Ming Deng; Zeyu Huang; Tingting Chen; Yu Chen; Bishao Sun; Yingbing Wu; Ronghua Wu; Qingjian Wu; et al. (Scientific Reports)
Abstract The incidence of prostate cancer (PCa) is high among elderly men. Cepharanthine hydrochloride (CH) is recognized for its important role in the prevention and treatment of various diseases. However, its effects and mechanisms of action in the context of PCa remain unclear. Our study aims to examine the therapeutic role and mechanisms of action of CH in PCa. Targets of CH and PCa-related genes were identified using different databases, and the biological processes through which CH might exert its therapeutic effects were predicted via protein–protein interaction (PPI) network and enrichment analyses. Subsequently, the PCa cell lines PC-3 and DU145 were used to assess the concentration- and time-dependent effects of CH on cell viability, proliferation, and migration. Transcriptomic sequencing and differential expression analysis were used to identify the key target protein of CH and the key signaling pathways involved in its therapeutic effects against PCa. Molecular docking was used to analyze the binding between CH and its target protein. Additionally, quantitative reverse transcription polymerase chain reaction (qRT-PCR), western blotting, gene knockout, pharmacological intervention, and tumor formation experiments were performed to validate the therapeutic effects and mechanisms of action of CH against PCa in vitro and in vivo. Network pharmacology showed that CH, a Chinese herbal medication, might prevent PCa by regulating protein phosphorylation-related biological processes. In vitro experiments showed that CH inhibited the proliferation and migration of PCa cells in a concentration-dependent manner. In addition, integration of transcriptomic sequencing, differential expression analysis, and GO enrichment analysis suggested that the ERK protein played a crucial role in the anti-tumor activity of CH. Molecular docking and molecular dynamics simulations revealed strong binding affinities between CH and ERK1/2. Further experimental verification, involving qRT-PCR, western blotting, gene knockout, pharmacological intervention, and tumor formation experiments, demonstrated that CH upregulated dual-specificity phosphatase (DUSP) 1 and suppressed the phosphorylation of ERK, thereby inhibiting the development and progression of PCa in vivo and in vitro. In conclusion, the findings of this study suggest that CH suppresses the ERK signaling pathway by enhancing the expression of DUSP1, thereby exerting anti-tumor effects against PCa in vitro and in vivo. Therefore, CH may serve as a novel therapeutic agent for PCa, showing remarkable potential for clinical application.